PARKINSON AND STEM CELL THERAPY - Gunawan, Gerry; Dalhar, Mochamad; Kurniawan, Shahdevi Nandar (Malang Neurology Journal, 2017)
Parkinson's disease is a neurodegenerative disorder that is progressive about the movement or control of movement. The disease often occurs in people over the age of 60 years. The etiology of Parkinson's disease caused by a combination of genetic and environmental factors. Because overall life expectancy increases, the number of people with Parkinson's disease will increase in the future. Treatment of Parkinson's disease can be used with pharmacological therapy and nonpharmacological therapy. Pharmacological therapy can use levodopa, monoamine oxidase-B inhibitors, dopamine agonists, anticholinergics and amantadine, while nonpharmacological therapies may use the method of stem cell therapy. Stem cells are master cells that have two important characteristics that can perform self-renewing through cell division and can be induced to become cells with specific functions. The aim of Stem cell therapy in Parkinson's disease to replace the damaged dopaminergic cells.